Technical efficiency and its determinants in the Indian meat processing industry - ABDULLA, ABDULLA; KUMAR, SHIV (The Indian Journal of Animal Sciences, 2021)
The stochastic frontier approach captures the technical efficiency and its determinants of meat processing industry using unit level data from 2002-2016 of annual survey of industries in India. The study concludes substantial (73%) scope of improvement in technical efficiency. Better management of inputs by private limited firms have achieved higher technical efficiency compared to firms of other sectors. Cross learning among best performing states and worst performing states would bridge the gap of technical efficiency in meat processing industry. The matching skill set of labour force with state of art technology is the way out to arrest the deterioration of technical efficiency in the industry.